2022
DOI: 10.1108/jicv-01-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Time headway distribution analysis of naturalistic road users based on aerial datasets

Abstract: Purpose Time headway (THW) is an essential parameter in traffic safety and is used as a typical control variable by many vehicle control algorithms, especially in safety-critical ADAS and automated driving systems. However, due to the randomness of human drivers, THW cannot be accurately represented, affecting scholars’ more profound research. Design/methodology/approach In this work, two data sets are used as the experimental data to calculate the goodness-of-fit of 18 commonly used distribution models of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Veng et al [10] proved that the type of vehicle has a significant influence on headway distribution, and the scenarios of car-car, car-truck, truck-truck and truck-car rarely appear in real traffic conditions, so the headway distribution model is analyzed separately for different types of vehicles. Also, by analyzing headway in the conditions of heterogeneous traffic flow, the truck-car ratio is included as one of specific variables for determining functional parameters [11]. Based on the research carried out in Iraq [12] on over 8000 headways, in order to determine the critical headway, it was found that the range of the critical interval was from 2.5 to 4 s, with a corresponding critical headway of 3.2 s on 10 measuring sections of the two-lane highways.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Veng et al [10] proved that the type of vehicle has a significant influence on headway distribution, and the scenarios of car-car, car-truck, truck-truck and truck-car rarely appear in real traffic conditions, so the headway distribution model is analyzed separately for different types of vehicles. Also, by analyzing headway in the conditions of heterogeneous traffic flow, the truck-car ratio is included as one of specific variables for determining functional parameters [11]. Based on the research carried out in Iraq [12] on over 8000 headways, in order to determine the critical headway, it was found that the range of the critical interval was from 2.5 to 4 s, with a corresponding critical headway of 3.2 s on 10 measuring sections of the two-lane highways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The obtained headway values are not of constant size in the same ambient conditions, so they mainly depend on the drivers' perceptive ability, processing of the received data, actions taken, and heterogeneous vehicle performance [16]. In the research [11] based on the use of two sets of experimental data for the calculation of headway values, 18 commonly used value distribution models were applied in order to select the best model. The study demonstrated a distribution model with adaptive parameters, and its performance and applicability were verified.…”
Section: Literature Reviewmentioning
confidence: 99%